Harnessing Bagasse Fiber via Wet Spinning Method - Binti Hashinoor, Nur Aida Afiqah; Kunchi Mon, Siti Zaharah (Progress in Engineering Application and Technology, 2025)
This study investigates the effect of treatment of sugarcane bagasse, a fibrous waste byproduct, into fibres via wet spinning. Sugarcane bagasse, typically abandoned or incinerated, releases greenhouse gases and pollutes the air. By transforming this agricultural waste into eco-friendly fibres, this research aims to enhance resource efficiency and environmental sustainability in the textile industry. The study systematically applied acid and alkaline hydrolysis treatments to bagasse fibres, improving their texture, softness, and homogeneity. Comparative tests evaluated the impact of various treatments on fibre characteristics. Fibres treated with NaOH and HCl exhibited enhanced softness and homogeneity, making them suitable for wet spinning extrusion. Further treatments with glucomannan and acetone successfully reconverted optimised fibres into continuous filaments, demonstrating their potential in textile applications. The findings indicate that sugarcane bagasse can serve as a viable alternative to synthetic fibres, fulfilling global demands for eco-friendly materials.